Genetic Counselors' Perspectives About Cell‐Free DNA: Experiences, Challenges, and Expectations for Obstetricians. Issue 6 (27th June 2018) - Agatisa, Patricia K.; Mercer, Mary Beth; Coleridge, Marissa; Farrell, Ruth M.
Abstract: The expansion of cell‐free fetal DNA (cfDNA) screening for a larger and diverse set of genetic variants, in addition for use among the low‐risk obstetric population, presents important clinical challenges for all healthcare providers involved in the delivery of prenatal care. It is unclear how to leverage the different members of the healthcare team to respond to these challenges. We conducted interviews with 25 prenatal genetic counselors to understand their experience with the continued expansion of cfDNA screening. Participants supported the use of cfDNA screening for the common autosomal aneuploidies, but noted some reservations for its use to identify fetal sex and microdeletions. Participants reported several barriers to ensuring that patients have the information and support to make informed decisions about using cfDNA to screen for these different conditions. This was seen as a dual‐sided problem, and necessitated additional education interventions that addressed patients seeking cfDNA screening, and obstetricians who introduce the concepts of genetic risk and cfDNA to patients. In addition, participants noted that they have a professional responsibility to educate obstetricians about cfDNA so they can be prepared to be gatekeepers of counseling and education about this screening option for use among the general obstetric population.